A High-Order Accurate Numerical Algorithm for the Numerical Solution of Burgers' Equation - Zorsahin Gorgulu, Melis (Muş Alparslan Üniversitesi, 2019)
Inthis study, a high accurate numerical solution of the Burgers’ equation isobtained. For this, the collocation method based on quintic B-spline functionsfor space discretization and the fourth-order single step method for timediscretization are used. In order to see the efficiency of the algorithm, atest problem with an analytical solution is discussed and compared with thenumerical solution obtained.

Buçalışmada, Burgers denkleminin yüksek doğruluklu bir sayısal çözümü eldeedilmiştir. Bunun için, konum ayrıştırmasında quintic B-spline fonksiyonlarınıtemel alan kolokasyon yöntemi ve zaman ayrıştırmasında dördüncü dereceden tekadımlı yöntem kullanılmıştır. Algoritmanın etkinliğini görmek için, analitikçözüme sahip bir test problemi ele alınmış ve elde edilen sayısal çözümler ilekarşılaştırılmıştır.
Burgers Denkleminin Nümerik Çözümü için Yüksek Dereceden Doğruluklu Nümerik Algoritma
msufbd
Keywords: Burgers'equation; Collocation method; fourth order single step method; quintic B-spline functions; Burgers denklemi; Dördüncü dereceden tek adımlı yöntem; Kolokasyon metodu; Kuintik B-spline fonksiyonları